Peroral endoscopic pyloromyotomy is efficacious and safe for refractory gastroparesis: prospective trial with assessment of pyloric function - Jacques, Jérémie; Pagnon, Lauriane; Hure, Florent; Legros, Romain; Crepin, Sabrina; Fauchais, Anne-Laure; Palat, Sylvain; Ducrotté, Philippe; Marin, Benoit; Fontaine, Sebastien; Boubaddi, Nour Edine; Clement, Marie-Pierre; Sautereau, Denis; Loustaud-Ratti, Veronique; Gourcerol, Guillaume; Monteil, Jacques (Endoscopy, 2019)
Background Gastroparesis is a functional disorder with a variety of symptoms that is characterized by delayed gastric emptying in the absence of mechanical obstruction. A recent series of retrospective studies has demonstrated that peroral endoscopic pyloromyotomy (G-POEM) is a promising endoscopic procedure for treating patients with refractory gastroparesis. The aim of this prospective study was to evaluate the feasibility, safety, and efficacy of G-POEM.Methods 20 patients with refractory gastroparesis (10 diabetic and 10 nondiabetic) were prospectively included in the trial. Patients were treated by G-POEM after evaluation of pyloric function using an endoscopic functional luminal imaging probe. Clinical responses were evaluated using the Gastroparesis Cardinal Symptom Index (GCSI), and quality of life was assessed using the Patient Assessment of Upper Gastrointestinal Disorders – Quality of Life scale and the Gastrointestinal Quality of Life Index scores. Gastric emptying was measured using 4-hour scintigraphy before G-POEM and at 3 months.Results Feasibility of the procedure was 100 %. Compared with baseline values, G-POEM significantly improved symptoms (GCSI: 1.3 vs. 3.5; P < 0.001), quality of life, and gastric emptying (T½: 100 vs. 345 minutes, P < 0.001; %H2: 56.0 % vs. 81.5 %, P < 0.001; %H4: 15.0 % vs. 57.5 %, P = 0.003) at 3 months. The clinical success of G-POEM using the functional imaging probe inflated to 50 mL had specificity of 100 % and sensitivity of 72.2 % (P = 0.04; 95 % confidence interval 0.51 – 0.94; area under the curve 0.72) at a distensibility threshold of 9.2 mm2/mmHg.Conclusion G-POEM was efficacious and safe for treating refractory gastroparesis, especially in patients with low pyloric distensibility.